Construction of carbocycles initiated by Cu-catalyzed radical reaction of Cl2C(CN)2. Issue 26 (29th June 2017) - Masuda, Keisuke; Tanigawa, Masashi; Nagatomo, Masanori; Urabe, Daisuke; Inoue, Masayuki
Abstract: A Cu-catalyzed radical reaction of Cl2 C(CN)2 was utilized for stereoselective conversion of unsaturated molecules into functionalized carbocycles. Chloromalononitrile radicals, generated by treating Cl2 C(CN)2 with catalytic amounts of CuCl and dppf in refluxing dioxane, intermolecularly reacted with the unsaturated bonds of acyclic or 10-membered compounds. The resultant carboradicals then intramolecularly added to another unsaturated bond to produce 1, 2-disubstituted cyclopentane or trans -decalin derivatives. The chemo- and stereoselectivities of these radical cascade reactions are discussed in detail. Graphical abstract: